Unveiling the impact of the SMARTCLAP project on habilitation - Matthew Bonello; Nathalie Buhagiar; Philip Farrugia; Joseph Mercieca (Computational and Structural Biotechnology Journal)
This report summarises the SMARTCLAP research project, which employs a user-centred design approach to develop a revolutionary smart product service system. The system offers personalised motivation to encourage children with cerebral palsy to actively participate more during their occupational therapy sessions, while providing paediatric occupational therapists with an optimal tool to monitor children’s progress from one session to another. The product service system developed includes of a smart wearable device called DigiClap used to interact with a serious game in an Augmented Reality environment. The report highlights the research methodology used to advance the technology readiness level from 4 to 6, acknowledging the contribution of the consortium team and funding source. As part of the technology’s maturity process, DigiClap and the respective serious game were evaluated with target users, to identify the system’s impact in supporting the children’s overall participation and hand function, and to gather feedback from occupational therapists and caregivers on this novel technology. The outcomes of this study are discussed, highlighting limitations and lessons learned. The report also outlines future work and further funding for the sustainability of the project and to reach other individuals who have upper limb limitations. Ultimately, the potential of DigiClap and the overall achievements of this project are discussed.